Identifying evidence of the effectiveness of photovoice: a systematic review and meta-analysis of the international healthcare literature - Halvorsrud, K; Eylem, O; Mooney, RM; Haarmans, M; Bhui, K (Oxford University Press, 2021)
Background: Photovoice (PV) was conceptualized in the early 1990s to engage community members in capturing/communicating their lived experience narratives through photography. However, no meta-analyses in health research have assessed whether PV achieves its purported effects.